Dietary supplementation of chestnut and quebracho tannins mix: Effect on caecal microbial communities and live performance of growing rabbits. (June 2019) - Turchi, Barbara; Mancini, Simone; Pastorelli, Roberta; Viti, Carlo; Tronconi, Laura; Bertelloni, Fabrizio; Felicioli, Antonio; Cerri, Domenico; Fratini, Filippo; Paci, Gisella
Abstract: The interest in antimicrobial compounds as feed additives is currently increasing. Among different options, tannins seem to have several beneficial effects when employed in animals diet. The present study aimed at investigating the influence on caecal microbial communities of the supplementation of a chestnut and quebracho tannins mix in meat rabbit's diet, also considering animals live performances. Four groups of rabbits were fed with a different diet: a control diet (C); a control diet with coccidiostat (CC), and two experimental diets with 0.3% (T0.3) and 0.6% (T0.6) chestnut and quebracho tannins mix. For microbial analysis, culture-dependent and culture-independent methods were employed. Live performances were not significantly affected by tannins mix supplementations, as well as culturable microbial loads of E. coli, Enterobacteriaceae, Bacteroides spp. and Bifidobacterium spp. C. perfringens was always under the detection limit. A consistent result was obtained by qPCR. As for PCR-DGGE analysis, the Richness and evenness (Shannon-Weiner index) of bacterial communities in caecum resulted significantly higher in control samples (C and CC) than in those from rabbit fed with tannin-containing diets. Sequencing analysis revealed that the phylum Firmicutes was less represented in samples from control groups. As for the methanogen archaeal DGGE, no significant differences were found in richness and diversity among different groups, all dominated by Methanobrevibacter spp.. This work highlights the potential antimicrobial effect of chestnut and quebracho tannins mix in an in vivo system revealed by molecular analysis. Highlights: Quebracho and chestnut tannins in rabbits diet affected caecum bacterial populations. Caecal methanogenic Archaea were not affected by tannins presence in the diet. PCR-DGGE showed decreased richness and evenness of caeacal bacterial communities. Caecal Firmicutes were less abundant in tannins-fed rabbits. Culture-dependent methods did not allow to detect tannins effect on bacteria.